A review of culture and implementation strategy among SMES in Zimbabwe - Nyamwanza, Tonderai (Academy of Business & Scientific Research, 2016)
The importance of SMEs development in the economic activities in Zimbabwe cannot be overemphasized. It has been acknowledged that organisational culture and strategy implementation are important to both the survival and growth of SMEs, and their continued contribution to economic growth. Despite this realisation, SMEs performance in Zimbabwe has continued to be marginal, hence the need to review the organisational culture and implementation linkage. This was a qualitative study using the multiple case study approach involving 8 organisations. In depth interviews and non-participant observations were used to collect data from owner/managers. There is evidence that SMEs undertake strategic planning and implantation, but there were no clear cultural changes to support both. The findings indicate that many SMEs owners are aware of the importance of culture in operations and strategy implementation but they tend to model organisations around a church and family framework with the hope that it will bring about better cohesion. However, these cultures tended to make the organisations perform at a suboptimal level as the owners' role will not be challenges under whatever circumstances.